Capacitively-Coupled Chopper Amplifiers - Fan, Qinwen; Makinwa, Kofi A. A.; Huijsing, Johan H. (Analog Circuits and Signal Processing,, 2017)
This book describes the concept and design of the capacitively-coupled chopper technique, which can be used in precision analog amplifiers. Readers will learn to design power-efficient amplifiers employing this technique, which can be powered by regular low supply voltage such as 2V and possibly having a +\-100V input common-mode voltage input. The authors provide both basic design concepts and detailed design examples, which cover the area of both operational and instrumentation amplifiers for multiple applications, particularly in power management and biomedical circuit designs. Discusses basic working principles and details of implementation for proven designs; Includes a diverse set of applications, along with measurement results to demonstrate the effectiveness of the technique; Explains advantages and drawbacks of the technique, given particular circumstances.